The effects of obesity information on IIUM students' health practices - Mohammed Zin, Nurul Haziqah (Malaysian Association of Communication Educators (MACE), 2021)
Most young adults nowadays are obese or are prone to becoming obese. As such, this study intends to explore students’ health practices after they are exposed to obesity-related information through mass media, new media, and interpersonal relationships such as family members, friends/colleagues, medical health officers, and social groups. The specific objectives of this study are: (a) to determine the level of IIUM students’ exposure to obesity, perceived susceptibility to obesity, perceived severity of obesity, perceived benefits from taking actions against obesity, and the perceived barrier to taking actions against obesity; (b) to determine the level of health practices among IIUM students; and (c) to determine the relationships of exposure to obesity, perceived susceptibility, perceived severity, perceived benefits, and perceived barriers resulting from obesity-related information with IIUM students’ health practices. This study employed a quantitative research design and used an online survey method with a network sampling technique to collect data. A total of 213 respondents participated in this study. The results of the study show that students tend to practice a healthy lifestyle after being exposed to obesity-related information through traditional and social media and also through interpersonal relationships, thus helping them further to prevent obesity. They know the severe effects of obesity and also the benefits of not being obese by practicing a healthy lifestyle.